2020
DOI: 10.1152/ajpheart.00647.2019
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac-specific inactivation of Prdm16 effects cardiac conduction abnormalities and cardiomyopathy-associated phenotypes

Abstract: A variant in the PRDM16 locus has been correlated with QRS duration in an electrocardiogram genome-wide association study, and the deletion of PRDM16 has been implicated as a causal factor of the dilated cardiomyopathy that is linked to 1p36 deletion syndrome. We aimed to determine how a null mutation of Prdm16 affects cardiac function and study the underlying mechanism of the resulting phenotype in an appropriate mouse model. We used cardiac-specific Prdm16 conditional knockout mice to examine cardiac functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(48 citation statements)
references
References 57 publications
3
44
0
1
Order By: Relevance
“…In line with its described role during cardiac development, 34,36 we observed severe cardiac defects in prdm16 morphants, precluding the visualization and reliable quantification of aortic anomalies. We therefore generated Tg(cmlc2:PRDM16) zebrafish which overexpress human fulllength PRDM16 in their cardiomyocytes.…”
Section: Prdm16 Controls Arterial Development In An Ec-autonomous Mannermentioning
confidence: 80%
See 2 more Smart Citations
“…In line with its described role during cardiac development, 34,36 we observed severe cardiac defects in prdm16 morphants, precluding the visualization and reliable quantification of aortic anomalies. We therefore generated Tg(cmlc2:PRDM16) zebrafish which overexpress human fulllength PRDM16 in their cardiomyocytes.…”
Section: Prdm16 Controls Arterial Development In An Ec-autonomous Mannermentioning
confidence: 80%
“…By detailed analysis of Prdm16's expression pattern across species, we provide evidence that Prdm16 co-defines arteriovenous identity of ECs in mammals and zebrafish across the vascular system, irrespective of developmental stage, anatomical location and hemodynamic factors. Studies in zebrafish embryos further revealed that the cardiovascular role of prdm16 extends beyond the heart muscle, 34,36 as prdm16 deficiency resulted in cell-autonomous arterial defects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BAT is the primary site of expression for Letmd1 (Figures 1B and S1A). In contrast, Prdm16 and Ebf2 exhibit more widespread tissue expression and regulate the development of vital tissues such as the brain, hematopoietic cells, and the cardiac conduction system (Aguilo et al, 2011;Bjork et al, 2010;Chuang et al, 2011;Kieslinger et al, 2010;Nam et al, 2020), which may explain why Prdm16 KO and Ebf2 KO are embryonic lethal. The Letmd1 KO mice are viable and grow normally (Figure 2B), and yet its BAT phenotype is more severe, resulting in defective BAT formation (Figures 3A, 3F, and 3K), impaired acute and chronic cold adaptation (Figures 2C and 4C), and increased susceptibility to diet-induced obesity (Figures 2H and 2I).…”
Section: Discussionmentioning
confidence: 99%
“…Последующие исследования подтвердили роль вариантов, приводящих к утрате копии PRDM16, в развитии НМЛЖ и дилатационной КМП у детей [18]. В экспериментах на нокаутированных по гену PRDM16 мышах была показана роль PRDM16 в развитии гипертрофической КМП [17,19] [16], однако для однозначного вывода о связи этого гена с НМЛЖ и первичными КМП имеющихся данных недостаточно.…”
Section: Discussionunclassified